UNDERSTANDING THE CONCEPT OF JUSTICE IN THE QURAN AND ITS IMPLEMENTATION IN ISLAMIC LAW - Haidi Hajar Widagdo; Zulkifli Zulkifli (Adisam Publisher, 2025)
The concept of justice enshrined in the Quran emphasizes the principles of balance, equality, and respect for individual rights regardless of one's social status, gender, or ethnic background. The Quran emphasizes the importance of social justice through the command to act justly even when faced with situations that challenge the individual or family, as stated in Surah An-Nisa verse 135. The verses remind us that the implementation of justice must include honesty in actions and avoiding discrimination and preconceptions. In addition, the Quran states the importance of justice in economic and political aspects, including through the zakat system and the prohibition of usury, which aim to reduce social disparities and ensure a more equitable distribution of wealth. These principles of justice also apply to governance, with an emphasis on integrity, transparency and accountability. The application of justice in Islamic law (sharia) is realized through various legal mechanisms and institutions that refer to Quranic principles. For example, Islamic criminal law contains specific provisions on fair legal procedures and the rejection of unfair or oppressive acts, while Islamic family law protects the rights of women and children and ensures fairness in the distribution of inheritance. However, there are significant challenges in implementing these concepts of justice uniformly across Muslim communities, largely due to differences in interpretation among the various madhhabs (schools) or schools of Islamic law, as well as the influence of state policies and political dynamics. Overcoming this imbalance requires wise policies and an unwavering commitment to the values of justice taught in the Qur'an.